2021
DOI: 10.1155/2021/5045250
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Adult Sacrococcygeal Teratoma Developing Adenocarcinoma: A Case Report and Review of Literatures

Abstract: Sacrococcygeal teratomas (SCT) are most commonly seen in infants and children but are rare in adults. Most adult SCT are benign and mature with a minority of tumors having immature components or overt malignancy. Here, we report a 65-year-old female with a SCT developing adenocarcinoma. The patient was diagnosed with benign sacrococcygeal cystic teratoma on her initial hospital visit and was treated with surgical resection. She was followed up postoperatively and was noted to have a markedly elevated CA 19-9 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The coccyx has full potential cells, and the risk of recurrence as well as the rate of malignant transformation associated with SCT may be associated with the absence of coccygectomy for surgery. Cui showed that the risk of recurrence can be as high as 30% to 40% if the SCT tumor is removed without removing the coccyx [8] ; Vana have reported a case of SCT that was surgically removed in the neonatal period, which recurred 31 years later and showed adenocarcinoma on postoperative histopathology, and they concluded that preservation of the coccyx at the first operation may be the cause of recurrence and malignant transformation. [9] These case reports remind us that thorough surgery, including complete resection of the SCT and coccyx, is an important means of preventing SCT recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The coccyx has full potential cells, and the risk of recurrence as well as the rate of malignant transformation associated with SCT may be associated with the absence of coccygectomy for surgery. Cui showed that the risk of recurrence can be as high as 30% to 40% if the SCT tumor is removed without removing the coccyx [8] ; Vana have reported a case of SCT that was surgically removed in the neonatal period, which recurred 31 years later and showed adenocarcinoma on postoperative histopathology, and they concluded that preservation of the coccyx at the first operation may be the cause of recurrence and malignant transformation. [9] These case reports remind us that thorough surgery, including complete resection of the SCT and coccyx, is an important means of preventing SCT recurrence.…”
Section: Discussionmentioning
confidence: 99%